LEARNING INNOVATION IN INTRODUCING NUMBER SYMBOL (ENGLISH) FOR CHILDREN - Ramadhani, Tasya Amelia; Purwanti, Ratna (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2024)
The problem in this research is motivated by the low activity and results of the development of language aspects in prounounce English numeral symbols. The causes of the problems are one-way learning, lack of child response and lack of variations in learning models. The solution is to use Pattern Model (Problem based learning model, mAke a match model, and Think, Talk, write and mEdia numbeR box). This study used a qualitative approach using Classroom Action Research (CAR) with 3 meetings, research settings in group B children at TK Aisyiyah Busthanul Athfal 36 Banjarmasin, totaling 18 children. The data collection technique is observation. Data analysis used descriptive analysis using tables and graphs. The results of this study concluded that the teacher's activities at meetings I and II achieved good criteria and at meeting III achieved very good criteria. The child's activity at meeting I reached the criteria of being inactive, meetings II and III reached the criteria of being very active. Classical completeness of child development results at meeting I reached 11%, meeting II reached 78% and meeting III reached 100%. It is recommended that teachers, school principals and further researchers be able to provide input and information for selecting learning models.